2020
DOI: 10.1371/journal.pone.0237081
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, perceptions, and behaviors impacting healthcare utilization of Syrian refugee children

Abstract: Background Approximately 18,000 Syrian refugees have resettled to the United States. Half of these refugees are children, whose age and refugee status jeopardize their abilities to attain quality healthcare. Information on Syrian refugees' health in the U.S. is limited. This qualitative study sought to explore Syrian refugee parents' beliefs, perspectives, and practices regarding their children's health through in-depth interviews. Methods Eighteen Syrian refugee parents residing in Cincinnati, Ohio were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(72 citation statements)
references
References 45 publications
2
69
1
Order By: Relevance
“…Current study results align with Woodgate et al (Woodgate et al, 2017), a study based in Manitoba, Canada, that demonstrated recent newcomers do not always understand how or where to access healthcare services. In the United States, Syrian refugee parents also reported numerous difficulties with navigating the healthcare system, often resulting in missed appointments for their children (Alwan et al, 2020) Theme 2: Limited awareness of healthcare services A few service providers and newcomers specifically mentioned not being aware of healthcare services. Many newcomers did not expect some healthcare services to be available simply because they are not offered in their home country, such as home care services.…”
Section: Theme 1: Navigation Difficultymentioning
confidence: 99%
See 4 more Smart Citations
“…Current study results align with Woodgate et al (Woodgate et al, 2017), a study based in Manitoba, Canada, that demonstrated recent newcomers do not always understand how or where to access healthcare services. In the United States, Syrian refugee parents also reported numerous difficulties with navigating the healthcare system, often resulting in missed appointments for their children (Alwan et al, 2020) Theme 2: Limited awareness of healthcare services A few service providers and newcomers specifically mentioned not being aware of healthcare services. Many newcomers did not expect some healthcare services to be available simply because they are not offered in their home country, such as home care services.…”
Section: Theme 1: Navigation Difficultymentioning
confidence: 99%
“…Several studies indicate lack of familiarity with the healthcare system is a barrier to accessing healthcare among newcomers (Wu et al, 2005;Son, 2013). A Syrian refugee parent noted that if a child is sick, they did not understand where to take the child to access appropriate care (Alwan et al, 2020). Similarly, Syrian refugees in Toronto, Canada expressed concerns regarding lack of accurate and user-friendly information about healthcare services (Guruge, Sidani, Illesinghe et al, 2018).…”
Section: Theme 1: Navigation Difficultymentioning
confidence: 99%
See 3 more Smart Citations